Earnings determination and taxes: evidence from a cohort based payroll tax reform in Greece - Emmanuel Saez; Manos Matsaganis; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2010)
This paper analyzes the response of earnings to payroll tax rates using a cohort-based reform in Greece. All individuals who started working on or after 1993 face permanently a much higher earnings cap for payroll taxes, creating a large and permanent discontinuity in marginal payroll tax rates by date of entry in the labor force for upper earnings workers. Using full population administrative Social Security data and a Regression Discontinuity Design, we estimate the long-term incidence and effects of marginal payroll tax rates on earnings. Standard theory predicts that, in the long run, new regime workers should bear the entire burden of the payroll tax increase (relative to old regime workers). In contrast, we find that employers compensate new regime workers for the extra employer payroll taxes but not for the extra employee payroll taxes. We do not find any evidence of labor supply responses around the discontinuity, suggesting low efficiency costs of payroll taxes. The non-standard incidence results are the same across firms of different sizes. Tax incidence, however, is standard for older workers in the new regime as they bear both the employee and employer tax. Those results, combined with a direct small survey of employers, can be explained by social norms regarding pay seniority which create a growing wedge between pay and productivity as workers age.
Keywords: J31; J22; H22; 330; Payroll taxes; Greece; Lohnsummensteuer; Steuerinzidenz; Einkommen; Griechenland